2019
DOI: 10.1016/j.neulet.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

CHRFAM7A alters binding to the neuronal alpha-7 nicotinic acetylcholine receptor

Abstract: Introduction: CHRFAM7A is a uniquely-human gene that encodes a human-specific variant of the alpha-7 nicotinic acetylcholine receptor (α7nAchR). While the homopentameric α7nAchR consists of 5 equal subunits, previous studies demonstrated that CHRFAM7A expression disrupts the formation of α7nAchR homopentamers. Here we use a rat neuronal cell line expressing CHRFAM7A and a transgenic mouse expressing CHRFAM7A to define the alpha-bungarotoxin (α-BTX) binding in vitro and in vivo. Methods: Rat PC12 cells were sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
5
13
0
Order By: Relevance
“…Based on the above data as well as on previous findings by our group and others in Xenopus oocytes and in several mammalian cell lines, such as neuroendocrine GH4C1, immune RAW264.7, BOSC-23 kidney, or human NSCLC cells ( 36 , 37 , 39 , 54 , 55 ), we propose that dupα7 subunits could be colocated with full-length α7 subunits in SH-SY5Y cells forming heteromeric dupα7/α7-nAChRs to the detriment of fully functional homomeric α7-nAChR expression. If our proposal is true, then overexpression of dupα7 in SH-SY5Y cells would result in a decreased cellular responsiveness to α7-nAChR stimulation.…”
Section: Discussionsupporting
confidence: 64%
“…Based on the above data as well as on previous findings by our group and others in Xenopus oocytes and in several mammalian cell lines, such as neuroendocrine GH4C1, immune RAW264.7, BOSC-23 kidney, or human NSCLC cells ( 36 , 37 , 39 , 54 , 55 ), we propose that dupα7 subunits could be colocated with full-length α7 subunits in SH-SY5Y cells forming heteromeric dupα7/α7-nAChRs to the detriment of fully functional homomeric α7-nAChR expression. If our proposal is true, then overexpression of dupα7 in SH-SY5Y cells would result in a decreased cellular responsiveness to α7-nAChR stimulation.…”
Section: Discussionsupporting
confidence: 64%
“…α-BTX showed very low binding affinity to all the receptors containing Dupα7 subunits ( Table 2), suggesting that those receptors will be resistant to α-BTX. This observation agrees with the published experimental data showing that CHRFAM7A decreased α-BTX binding as detected by immunohistochemistry and flow cytometry and markedly decreased α-BTX staining neuromuscular junction of CHRFAM7A transgenic mice (Chan et al, 2019).…”
Section: The Effect Of Dupα7 Subunits On Macromolecular Ligand Bindingsupporting
confidence: 93%
“…Nearly 20 y ago, the possibility that taxonomically restricted genes specify species-specific responsiveness garnered attention with the discovery of cmah (7), a gene whose product is absent in humans but nevertheless regulates resilience, susceptibility, and the response to infection and injury in other species (8, 61, 62). The present study with CHRFAM7A in transgenic mice was made possible because we were first able to show that CHRFAM7A recognizes and regulates the mouse form of α7nAChR (19). We posit that it is this interaction that most likely generates the HSC phenotype reported here and predict that CHRNA7 knockout mice could have the same phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have suggested that CHRFAM7A encodes a dominant-negative inhibitor of ligand binding to α7nAChR in vitro (1518), which can also be observed at the neuromuscular junction of transgenic mice (19). As such, CHRFAM7A has been implicated in the regulation of numerous α7nAChR-dependent antiinflammatory processes as well as in mental health, cognition, and neurodegenerative disease (20).…”
mentioning
confidence: 99%